Stress corrosion cracking behavior of super 13Cr tubing in phosphate packer fluid of high pressure high temperature gas well. (September 2022) - Fu, Anqing; Long, Yan; Liu, Hongtao; Zhao, Mifeng; Xie, Junfeng; Su, Hang; Li, Xuanpeng; Yuan, Juntao; Lei, Xiaowei; Yin, Chengxian; Feng, Yaorong
Highlights: The failure mode of super 13Cr tubing is brittle transgranular fracture, which is initiated from the outer surface of the tubing. The main cause of SCC failure of 13Cr tubing is the synergistic effect KH2 PO4 phosphate packer fluid and CO2 . Cracks initiated from the corroded martensitic multiscale boundaries, and propagated due to the low structure strength of the corrosion damaged zone. 13Cr tubing exhibited substantially low SCC susceptibilities in formate, which is a candidate packer fluid suitable for HPHT gas wells. Abstract: This paper describes a stress corrosion cracking (SCC) failure case of super 13Cr tubing serviced for six years in a high-pressure, high-temperature (HPHT) gas well. The failure causes and processes were studied by various characterizations and SCC simulation testing. The failure mode of super 13Cr tubing is brittle transgranular fracture, and the dominating role in SCC failure is the synergistic action of KH2PO4 phosphate packer fluid and CO2, leading to corrosion damaged zone, which is a selective corrosion along the martensitic multiscale boundaries. Under tensile stress, cracks developed at the corroded martensitic multiscale boundaries and propagated due to the low structural strength of the corrosion-damaged zone. Due to its compatibility with 13Cr tubing, formate is recommended as an alternate packer fluid for high-pressure, high-temperature (HPHT) gas wells.